Clinical features and genotypes of six patients from four families with horizontal gaze palsy with progressive scoliosis - Huang, Lijuan; Guo, Jianlin; Xie, Yan; Zhou, Yunyu; Wu, Xiaofei; Li, Hui; Peng, Yun; Li, Ningdong (Frontiers in Pediatrics, 2022)
Background: Horizontal gaze palsy with progressive scoliosis (HGPPS) is a rare disorder mainly involved in ocular movement and spinal development. It is caused by a roundabout guidance receptor 3 (ROBO3) gene mutation. This study aimed to describe the clinical features of six patients with HGPPS and investigate the corresponding ROBO3 gene mutations. Methods: Patients underwent detailed clinical and imaging examinations. Whole-exome sequencing was performed to detect nucleotide variations in the disease-causing genes of HGPPS. Results: Six pathogenic variants were detected in the ROBO3 gene from six patients with HGPPS, including two novel compound heterozygous mutations, c.1447C>T (p.R483X) and c.2462G>C (p.R821P); c.1033G>C (p.V345L) and c.3287G>T (p.C1096F); a novel homozygous indel mutation, c.565dupC (p.R191Pfs*61); and a known missense mutation, c.416G>T (p.G139V). Patients with HGPPS had horizontal conjugated eye movement defects and scoliosis with variable degrees, as well as flattened pontine tegmentum and uncrossed corticospinal tracts on magnetic resonance imaging. Conclusions: Our genetic findings will expand the spectrum of ROBO3 mutations and help inform future research on the molecular mechanism of HGPPS.